Peroneus brevis tendon injury in chronic ankle instability.: A comparative study - Daniel , Rhavi Soares; Maluf Neto, Joaquim; Okamoto, Auro Mitsuo; Andrade, Carlos (Journal of the Foot & Ankle, 2021)
Objective: To compare the surgical outcome of patients with chronic lateral ligament injury of the ankle, with and without an associated peroneus brevis tendon injury. Methods: This retrospective comparative study was based on epidemiological analysis and the American Orthopedic Foot and Ankle Society (AOFAS) scores of patients diagnosed with chronic ankle instability who were treated surgically with the Broström-Gould technique. The medical records of 50 patients treated in an orthopedics service between January 2012 and January 2020 were analyzed. The patients were divided into two groups: those with and without a peroneus brevis tendon injury. The following data were also collected: sex, age, comorbidities, and AOFAS score in the pre- and postoperative period (between 90-120 days), as well as other epidemiological data. Results: Sixteen patients (32%), whose mean age was 43 years and 76% of whom were female, presented with a peroneus brevis tendon injury. The right side (54%) was more commonly affected. The main comorbidities were obesity (14%), slight pes cavus (12%), diabetes mellitus (4%) and depression (4%). The mean improvement in AOFAS score was 41 points. There was a marginal difference in final AOFAS score (p=0.03) between the groups. Conclusion: The Broström-Gould Technique proved effective for treating chronic lateral ligament injury regardless of an associated peroneus brevis tendon injury. However, the final postoperative results were significantly worse in patients with a peroneus brevis tendon injury than in those without one. Level of Evidence III; Therapeutic Studies; Comparative Retrospective Study.